Potensi Pakan Burung Air Pada Ekosistem Rawa Aopa Taman Nasional Rawa Aopa Watumohaoi Sulawesi Tenggara - Muh Iksan; Jarwadi Budi Hernowo; lilik Budi Prasetyo (Jurnal Penelitian Pendidikan IPA, 2025)
The Aopa Wetland Ecosystem, a Ramsar site, supports 1% of global species, including diverse waterbirds. However, populations are under serious threat from human activities, especially illegal hunting that disturbs habitats. The decline of waterbirds in Aopa Watumohai National Park (TNRAW) is the highest compared to other Indonesian national parks. This study, conducted from January to March 2023, aimed to analyze waterbird food resources through field observations. Data collected included distribution, number of species and individuals, diversity (Shannon index), and food types. Observations were carried out by boat across swamp areas. Results recorded 17 species of waterbirds totaling 1,217 individuals, with the highest abundance in open vegetation dominated by Irediparra galinacea (23.2%). Food resources were identified from 418 individuals representing 14 species, grouped into four classes: Insecta (5 species), Pisces (5), Gastropoda (3), and Malacostraca (1). The observation area was classified into vegetation types: open (VT), closed (VTP), and water body (BA). VT provided 14 food types, VTP 13 types, and BA 11 types. These findings emphasize the importance of protecting wetland habitats to sustain waterbird populations in TNRAW.